Możliwości wdrożeń koncepcji zarządzania przez jakość (TQM) w klubach sportowych = The ability to implement TQM in sport clubs - Tomanek, Mateusz; Markuszewski, Zdzisław (Journal of Education, Health and Sport, 2016)
Mateusz Tomanek, Zdzisław Markuszewski. Możliwości wdrożeń koncepcji zarządzania przez jakość (TQM) w klubach sportowych = The ability to implement TQM in sport clubs. Journal of Education, Health and Sport. 2016;6(9):966-974. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.212376 https://pbn.nauka.gov.pl/sedno-webapp/works/769709 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Pola nd Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License ( http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.09.2016. Revised 22.09.2016. Accepted: 30.09.2016. Streszczenie W artykule dokonano analizy możliwości wdrożenia TQM w klubach sportowych, oraz przedstawiono w jaki sposób można wykorzystać narzędzia stosowane w TQM w organizacjach sportowych. Słowa kluczowe: TQM, sport, klub sportowy, jakość, zarządzanie Abstract This paper provides an analysis of the ability to implement TQM in sport clubs, depicting the manner in which TQM tools can be used by said clubs. Keywords: TQM, sport, sport club, quality, management